182k views
3 votes
Y = -3x + 1
4x + y = 3
Eions?
What is the solution to the system of equations

1 Answer

7 votes

Answer:

(2, - 5 )

Explanation:

Given the 2 equations

y = - 3x + 1 → (1)

4x + y = 3 → (2)

Substitute y = - 3x + 1 into (2)

4x - 3x + 1 = 3

x + 1 = 3 ( subtract 1 from both sides )

x = 2

Substitute x = 2 into (1) for corresponding value of y

y = - 3(2) + 1 = - 6 + 1 = - 5

solution is (2, - 5 )

User Paulcm
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.